Influence of the Level of Defective Insulation Resistance of Electrical Machine Windings on Parameters of no-Load Current - A. V. Isaev; Yu. V. Suhodolov; S. V. Sizikov; A. A. Lomtev; V. A. Lychkovsky (Приборы и методы измерений, 2024)
Diagnostic methods that will change at present for monitoring the condition of windings of electric machines do not allow to detect defect formation in them at early stages of development. And this problem is especially relevant for equipment that is directly in its operating mode. The purpose of the work was to consider and evaluate the possibility of a method that, based on the analysis of the parameters and characteristics of the no-load current, will allow to characterize the state of the current-carrying parts of the windings of diagnosed electric machines. The paper presents the results of experimental studies of the patterns of influence of the level of defective resistance of interturn insulation in the windings of electric machines on the parameters of the no-load current, including the features of changes in the parameters of its spectral components. The article also defines analytical dependencies of the obtained characteristics of influence and analyzes the factors that determine the measurement errors of the developed method. The presented method based on the analysis of the parameters of the spectral components of the no-load current is intended for measuring the resistance of the interturn insulation of current-carrying parts in the windings of electrical machines under their operating conditions, with the possibility of recording the onset of defect formation, which will allow real-time assessment of its operational, pre-failure and serviceable state.